Knowledge, Attitude, and Practice of Blood Donation Among Male Students of University of Science and Technology, Sana'a, Yemen, 2026 - Wahas, Abdulraheem Yahya Ahmed; Labyadh, Abdullah Badr Abdullah; Al-Attas, Abdul Qader Mohammed; Al-Ahdal, Ammar Abdulrahman; Qhazi, Marwon Mohammed Abdullah; Jafar, Taha Muhammad Derhem (My University, 2026)
Background: Blood transfusion is one of the most essential needs to manage patients suffering from various medical conditions. Nowadays, voluntary blood donors are the only source of blood in the blood banks. There is a great need to create awareness among the population at large and students about blood donation to maintain a regular blood supply. University students can be used as best model to lead this initiative. Objective: The aim of this study was to assess the knowledge, attitude and practice regarding blood donation among undergraduate UST students.